Coefficient estimates for a subclass of bi-univalent functions associated with the Salagean differential operator - Shabani, Mohammad Mehdi; Yazdi, Maryam; Sababe, Saeed Hashemi (Annals of Mathematics and Physics, 2024)
In this paper, we present and examine a novel subset of the function class ∑, which consists of analytic and bi-univalent functions defined in the open unit disk U and connected to the Salagean differential operator. Additionally, we determine estimates for the Taylor-Maclaurin coefficients |a2| and |a3| functions within this new subclass and enhance some recent findings. 2010 Mathematics Subject Classification. 30C45; 30C50.